2010
DOI: 10.1007/s00381-009-1071-8
|View full text |Cite
|
Sign up to set email alerts
|

Perimedullary arteriovenous fistulas in pediatric patients: clinical, angiographical, and therapeutic experiences in a series of 19 cases

Abstract: PMAVFs in pediatric population exhibit many characteristics in clinical and angiographical aspects, need for special considerations. Most of PMAVFs in pediatric patients are high-flow fistulas, and endovascular embolization should be the first choice of treatment. After appropriate therapy, most of children can get satisfactory outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 16 publications
1
16
0
Order By: Relevance
“…Some authors reported that spinal cord deficits associated with a consistent portion of the menstrual cycle may suggest the possibility of an arteriovenous malformation of the spinal cord [43]. Of intradural AVMs, 3.2-5.1% were associated with various syndromic associations, including Cobb, Klippel-Trenaunay-Weber, Parkes Weber, or Rendu-Osler-Weber diseases [15,23,42]. Spontaneous thrombosis of the perimedullary AVF and intramedullary AVM, although often referred to by those who oppose interventional treatment [44], is, in fact, rare (0.7%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some authors reported that spinal cord deficits associated with a consistent portion of the menstrual cycle may suggest the possibility of an arteriovenous malformation of the spinal cord [43]. Of intradural AVMs, 3.2-5.1% were associated with various syndromic associations, including Cobb, Klippel-Trenaunay-Weber, Parkes Weber, or Rendu-Osler-Weber diseases [15,23,42]. Spontaneous thrombosis of the perimedullary AVF and intramedullary AVM, although often referred to by those who oppose interventional treatment [44], is, in fact, rare (0.7%).…”
Section: Discussionmentioning
confidence: 99%
“…(Table 2) and can be treated via both endovascular and direct surgical approaches. Coils, glues, and balloons have all been used to embolize these fistulae [14,15,20]. Most of perimedullary AVFs in pediatric patients are high-flow fistulas, and endovascular embolization should be the first choice of treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meng et al studied 19 child PMAVF cases in 2010, and in this limited study, the treatment outcomes were satisfactory. Of the 14 children who were followed-up, 42.9% (6/14) were succefully treated and 7 (50%) had greatly improved (79). Cervical PMAVFs can also achieve good therapeutic outcomes, as identified by Endo et al In that study, 20 of 22 patients were rated as having a good recovery 6 months after surgery (20).…”
Section: Therapeutic Outcome Of Spinal Cord Pmavfsmentioning
confidence: 96%
“…[39], [41] PMAVF is usually diagnosed between the third and sixth decades of life and are very rare, particularly in children. [42]The exact prevalence of PMAVFs is unknown but it is estimated that they constitute 4%-40% of spinal AVMs. [43], [44] Although the thoracolumbar spinal cord is the most common site of PMAVFs, these lesions can be seen at cervical and thoracic levels as well.…”
Section: Pmavfsmentioning
confidence: 99%